2021
DOI: 10.1080/26895293.2021.1931477
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of histone H3 lysine 9 methylation in inflammation

Abstract: Inflammation is a defense mechanism that the immune system uses in response to harmful stimuli such as pathogens, damaged cells, toxic compounds, or irradiation. These stimuli may induce inflammatory response and potentially tissue damage in respiratory, cardiovascular, digestive, nervous, endocrine, urinary, or reproductive systems. Inflammatory diseases include a broad array of disorders and conditions that are characterized by inflammation, ranging from autoimmune disease, atopic dermatitis, asthma, chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 131 publications
0
2
0
Order By: Relevance
“…As previously mentioned, H3K9 methylation regulates multiple inflammatory pathways and therefore, we next tested directly whether NSP1 expression influenced H3K9 dimethylation [38,39]. ChIP-seq with specific anti-H3K9me2 antibodies yielded the expected pattern of chromatin modifications at genic loci (S2D Fig).…”
Section: Plos Onementioning
confidence: 85%
See 1 more Smart Citation
“…As previously mentioned, H3K9 methylation regulates multiple inflammatory pathways and therefore, we next tested directly whether NSP1 expression influenced H3K9 dimethylation [38,39]. ChIP-seq with specific anti-H3K9me2 antibodies yielded the expected pattern of chromatin modifications at genic loci (S2D Fig).…”
Section: Plos Onementioning
confidence: 85%
“…A recent study showed NSP1 interacting with PRRC2B [32], a poorly characterized protein that has been proposed to regulate translation, and also has been found to interact with EHMT2/ G9a [35][36][37]. G9a is a Histone H3 Lysine 9 (H3K9) mono-and di-methyl transferase setting repressive H3K9me and H3K9me2 marks that are known to regulate multiple inflammatory pathways [38][39][40][41][42]. Most importantly, PRRC2B along with the translation initiation factors eIF3a/eIF3G and Ribosomal Proteins RPS10/RPS10 are the only proteins among the strong interactants that lose affinity with the K164A/H165A in both C-terminal and N-terminal NSP1 tagging systems (S2A Fig) . This implies that any comparison of the WT vs K164A/ H165A may include a PRRC2B-mediatied effect.…”
Section: Plos Onementioning
confidence: 99%